THE PERSONS DEPRIVED OF LIBERTY, AS PASSIVE SUBJECT OF THE CRIMINAL EXECUTION LEGAL RELATIONSHIPS - Simona Cireșica OPRIȘAN (Challenges of the Knowledge Society, 2019)
The study analyzes the behaviour of individuals deprived of their liberty both as an individual phenomenon and in relations established during the execution of custodial sentences. The impact of detention on these people is different, so their reactions are different. Isolation of society, loss or restriction of rights, separation from their families, subjection to a severe life regime, all perceived as a violation of his integrity as a human being. The study also analyzes the conformism/discipline report, taking into account both personal factors and secondary (environmental) factors generating aggressive behaviours, circumstances that affect the psyche of a person deprived of liberty, lowering his tolerance to everything the authorities involve who consider them “malevolent entities” whose purpose is to punish the innocent, to destroy the prisoner's being by being subjected to ill-treatment or by applying disciplinary sanctions. The study also focuses on the relationship between the person deprived of liberty and the restorative justice, the relationship between the offender, the victim, the criminal trial, the criminal sanction, the prison, in order to identify adequate remedies in order to recover the damage caused by the offense, as an alternative to the retributive penal system, focusing on the dialogue, on the negotiation, to enable offenders to assume active responsibility for their actions.